تقييم المشاريع الصناعية في المناطق الحرة في العراق اشارة خاصة الى المنطقة الحرة في محافظة نينوى - د. عبد الغفور حسن كنعان; ضحى سالم أحمد (PROSPECTIVE RESEARCHES, 2023)
Investment is regarded as the main motivator for the economic activity, specially industrial projects. This of course, requires the preparation of a study for economic efficiency and quality for the project that is intended to be executed. This, therefore, is regarded as one of the important evaluation for decision making in selecting the investment projects in the industrial development process, which characterizes the economic resources of scarcity, especially in the developing countries. The establishment of free zones in Iraq has led to the openness to the foreign world and benefit from the success of others, experiences in the sphere of channels diversity to acquire the resources especially foreign currencies that support the national economy and transfer the knowledge in all forms and productive techniques for the country. It also provides employment opportunities and participate in the training and skill opportunities in these which lead in the end, to achieve the economic development objectives for the country.